Hak al-Irtifaq (Ø§Ù„Ø§Ø±ØªÙØ§Ù‚) Menurut Islam (Sains Humanika, 2018)
This paper discusses the concept of the rights of al-irtifaq (ØÙ‚ Ø§Ù„Ø§Ø±ØªÙØ§Ù‚) which has been discussed by scholars since so long, and its related to the rights in using an immovable property by the society. In an increasingly modern and evolving community of life, there will be a community of people who are pursuing their own interests, forgetting about the importance of preserving this al-irtifaq rights (ØÙ‚ Ø§Ù„Ø§Ø±ØªÙØ§Ù‚). The views of the scholars from four schools of thought are discussed in this paper aiming at highlighting the importance of preserving some of the essential rights encompassed in the rights of al-irtifaq (ØÙ‚ Ø§Ù„Ø§Ø±ØªÙØ§Ù‚) so that the community is reminded of the necessary and necessity of those rights. These views are based on literature studies which involve references to their books. From the outcome of the discussion on the concept of the rights of al-irtifaq (ØÙ‚ Ø§Ù„Ø§Ø±ØªÙØ§Ù‚), it is found that past scholars gave emphasis since long time ago on these rights to ensure that no member in any community has adverse effects in everyday life. Therefore, there should be individuals and certain groups who fulfill the duty of reprimanding and teaching and reminding to ensure that the society always preserve these rights.
Keywords: The concept of al-irtifaq rights; four school of thought scholars; harmness; maintenance of rights.